Orthodontic Management of Pseudo Class III Malocclusion: A Case Report - Chaudhary, Nabin Kumar; Giri, Jamal; Pokharel, Prabhat Ranjan (Journal of BP Koirala Institute of Health Sciences, 2022)
Pseudo class III malocclusion is due to immature contact of incisors resulting in a forward shift of mandible. A 13-year-old male patient presented with the complaint of inability to bite properly with pseudo skeletal class III malocclusion, functional shift, and reverse overjet which was treated with fixed orthodontic treatment. The total treatment duration was 21 months in which correction of the discrepancy between centric occlusion and centric relation and improvement of the smile of the patient was achieved. Early and timely diagnosis of pseudo class III malocclusion will lead to a successful outcome with fixed orthodontic therapy.